POPULARITAS KESENIAN JARANAN SENTHEREWE DI KABUPATEN TULUNGAGUNG - Rokhim, Nur (Greget Jurnal Pengetahuan dan Penciptaan Tari, 2013)
Jaranan Sentherewe is a folk art from the Tulungagung regency which continues to existand thrive to the present day. This art form was created in the 1980s to replace the arts of jarananJawa and jaranan Pegon which had existed since 1949. Originally Jaranan Sentherewe was dancedby ludruk artists and as such, the movements were taken from the vocabulary of remo movementsfrom East Java. The presence of Jaranan Sentherewe provided a new spirit for theTulungagung community, as seen in their enthusiasm and the form of dynamic movements used.Its popularity has increased with the new developments in technology that have accompanied it.As a form of folk art, Jaranan Sentherewe cannot escape its function as a form of entertainment,catering to the taste of the community which is increasingly inclined towards the pop culture.Several innovations have been made to ensure that Jaranan Sentherewe continues to exist and itsperformances are still enjoyed by audiences. Performances aim to satisfy audiences by means ofactive interaction. The proof of such interaction can be seen when the dancers experience what isknown as ndadi. Some member of the audience also experience ndadi when listening to the monotonousjaranan music. This ndadi scene is awaited eagerly by the audience who are keen towitness the dancers’ movements when they experience a state of ndadi. In this way, the art ofJaranan Sentherewe cannot be separated from its supporting community, in terms of its existenceand also its form of performance which is always integrated with the audience.